Economic viability and profitability assessments of WECS - Mohammed Kdair Abd (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Technical and technological advances in alternative energy sources have led many countries to add green energy to their power plants to reduce carbon emissions and air pollution. At present, many electricity companies are looking to use alternative sources of energy because of high electrical energy prices. Wind energy is more useful than many renewable energies such as solar, heat, biomass, etc. The Wind Energy Conversion System (WECS) is a system that converts the kinetic energy of the wind into electrical energy to feed the known loads. WECS can be found in a variety of technology. Climate change and load demand are essential determinants of WECS optimization modelling. In this paper, proposed a strategy focused primarily on economic analysis WECS. The strategy based on a weather change to find the optimal designing and modelling for four different types of WECS using HOMER software. Finally, several criteria were used to determine which type of WECS was the most profitable investment and less payback period.